COVID‐19 field instruction: Bringing the forests of British Columbia to students 8, 000 km away. Issue 1 (10th March 2021) - Culbert, Patrick D.
Abstract: Field instruction is a crucial component of natural sciences education. The COVID‐19 pandemic has shifted many university courses to an online format, significantly impacting field instruction. FRST 350, Foundational Field School, is an 8‐day University of British Columbia Forestry field course taught to incoming transfer students from partner universities in China. In August 2020, I taught this course online to students studying remotely. In re‐developing the course, I spent 9 days in the field filming high definition (HD) video, 360° video, and 360° photography to best recreate the course in a short time‐frame. A 360° video records omnidirectionally, allowing viewers to "look around" in all directions, resulting in a highly immersive experience. Students expressed favorable opinions of the course, especially traditional HD and 360° video. Students generally preferred HD videos over 360°, though this was due mostly to the high bandwidth needed for 360° video and the fact that core course content was primarily conveyed as HD videos (in recognition of bandwidth challenges), with supplementary 360° videos. Students favorably noted the interactivity and immersive feel of 360° videos and photographs. This technology is financially and logistically feasible for use in a natural sciences course. Instructors engaged in online field instruction should weigh the strengths and weaknesses of various technologies, including 360° video, when determining how to best meet their learning objectives.